SLC25A42 promotes gastric cancer growth by conferring ferroptosis resistance through enhancing CPT2-mediated fatty acid oxidation - Haoying Wang; Weijia Dou; Mengxiao Liu; Weifang Wang; Ying Yang; Jibin Li; Zhenxiong Liu; Nan Wang (Cell Death and Disease)
Abstract Accumulating evidence has shown that the dysfunction of mitochondria, the multifunctional organelles in various cellular processes, is a pivotal event in the development of various diseases, including human cancers. Solute Carrier Family 25 Member 42 (SLC25A42) is a mitochondrial protein governing the transport of coenzyme A (CoA). However, the biological roles of SLC25A42 in human cancers are still unexplored. Here we uncovered that SLC25A42 is upregulated and correlated with a worse prognosis in GC patients. SLC25A42 promotes the proliferation of gastric cancer (GC) cells while suppresses apoptosis in vitro and in vivo. Mechanistically, SLC25A42 promotes the growth and inhibits apoptosis of GC cells by reprograming lipid metabolism. On the one hand, SLC25A42 enhances fatty acid oxidation-mediated mitochondrial respiration to provide energy for cell survival. On the other hand, SLC25A42 decreases the levels of free fatty acids and ROS to inhibit ferroptosis. Moreover, we found that SLC25A42 reprograms lipid metabolism in GC cells by upregulating the acetylation and thus the expression of CPT2. Collectively, our data reveal a critical oncogenic role of SLC25A42 in GCs and suggest that SLC25A42 represent a promising therapeutic target for GC.